(In)effective communication about social responsibility? Examining large European businesses in the Czech Republic - Macgregor Pelikanova, Radka; Nesbitt, Todd; Balcerzak, Adam P.; Oulehla, Jiri (Business, Management and Economics Engineering, 2024)
Purpose – Businesses are expected to be socially responsible by engaging in Corporate social responsibility (CSR) and even the Creation of shared values (CSV). The aim of this contribution is to critically explore whether large European businesses operating in Czechia, recognized as social responsibility leaders, effectively communicate CSR as opposed to their competitors. Research methodology – A case study with three stages was conducted. First, 35 large European businesses were identified, which repeatedly ranked among the TOP 25 Czech companies with the highest social responsibility BpS synthetic index, and their 15 competitors. Second, an Internet search and content analysis of Websites of these 50 companies was performed to categorize and assess how they report about their socially responsible behaviors. Third, leading Czech disinformation websites were examined for evidence of tacit cooperation with the disinformation scene in the form of support via advertising. Findings – The study revealed that large European businesses, recognized as social responsibility leaders, communicate extensively about their social responsibility. However, the effectiveness of such communications is controversial. In addition, a significant part of these businesses were found to be tacitly associated with disinformation platforms, which are completely at odds with with basic social responsibility concepts. Research limitations – The qualitative nature of the case study does not allow direct generalizations. Practical implications – The visualization of the juxtaposed results via comparative and complementary tables leads to pioneering propositions about the interest and lack of maturity regarding social responsibility, very diverse degrees of effectiveness of the communications, and even several alleged leaders failing in their efforts. Originality/Value – It is the first study to compare CSR communications by alleged white sheep and black sheep, while having consistency tested by association with disinformation websites. The generated propositions call for further longitudinal and multi-jurisdiction studies to verify and enhance the awareness about efficient, effective, mature and consistent social responsibility in the EU.